O Mecanismo do Desempenho Eletroanalítico dos Derivados Triazólicos de Ferroceno e Polímeros Condutores na Eletrodetecção de Fármacos e Pesticidas e a Sua Descrição Matemática - Tkach, Volodymyr Valentynovych; Ojani, Reza; Espínola, Michel O. G.; Blanes, Montserrat; Yelenich, Olga; Yagodynets´Petro (Orbital: The Electronic Journal of Chemistry, 2016)
A mechanism was suggested for the electroanalytic function of triazolic ferrocene derivatives in the electrochemical detection of pesticides and drugs, with the emphasis on the behavior of triazole ring. The suggested mechanism was mathematically represented, by form of analysis (by means of linear stability theory and bifurcation analysis) and development of a mathematical model. The result of the modeling has been compared with the result of experimental observations. DOI: http://dx.doi.org/10.17807/orbital.v8i4.690